2020
DOI: 10.1186/s13033-020-00416-0
|View full text |Cite
|
Sign up to set email alerts
|

Responding to mental health needs of Syrian refugees in Turkey: mhGAP training impact assessment

Abstract: Background About 1468 Syrian and Turkish doctors, serving in primary health care, have received the mhGAP training during 2016–2019. As additional training needs were identified, MoH and WHO wanted to understand the usefulness of the training and its impact in responding to the mental health needs of Syrian refugees in Turkey. Methods A five component assessment was done in 2019, consisting of feedback of trainees, assessment of increase in knowledge; utilization of service; compliance to treatment guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…Over the last decade, various new tools have been developed with the goal of scaling-up delivery of MNS services through task-sharing approaches aimed at improving mental health coverage among refugee populations (e.g., the mhGAP-HIG) [ 21 ] and considerable efforts have been made to train and supervise staff with these methods in some regions [ 22 , 35 37 ]. An evaluation of mhGAP-HIG capacity building efforts in refugee camps in seven sub-Saharan African countries showed various effects such as (1) strengthened capacities by facility- and community-based staff to deliver mental health and psychosocial support interventions, (2) positive changes in their attitudes towards people suffering from MNS conditions, and (3) improved collaboration among health and non-health staff regarding people suffering from MNS conditions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, various new tools have been developed with the goal of scaling-up delivery of MNS services through task-sharing approaches aimed at improving mental health coverage among refugee populations (e.g., the mhGAP-HIG) [ 21 ] and considerable efforts have been made to train and supervise staff with these methods in some regions [ 22 , 35 37 ]. An evaluation of mhGAP-HIG capacity building efforts in refugee camps in seven sub-Saharan African countries showed various effects such as (1) strengthened capacities by facility- and community-based staff to deliver mental health and psychosocial support interventions, (2) positive changes in their attitudes towards people suffering from MNS conditions, and (3) improved collaboration among health and non-health staff regarding people suffering from MNS conditions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result may also point to the importance of clinician-patient relationship and the care received. In another interview-based qualitative study that was conducted by World Health Organization and Ministry of Health on Syrian refugees receiving mental health care and psychosocial support, the results showed that the satisfaction level and 'having needs met' were high among participants (Kahiloğulları et al, 2020).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…Klavuz, afet ve acil durumlarında ve sağlık kapasitesinin kısıtlı olduğu durumlarda, birinci basamak sağlık hizmetlerinde çalışan sağlık personelinin ruh sağlığı hizmeti sunabilmesi için, psikiyatrik, nörolojik ve madde kullanımı sorunlarının yönetimi için yönergeler içermektedir (35). Türkiye'de yapılan bir çalışmada (36), RSGÜÇ uygulamasının, hizmet sunan doktorların ruh sağlığına ilişkin bilgi düzeyini arttırdığı, tespit edilen vakaların sayısın arttığı, bu hizmeti alan mültecilerin büyük kısmının (%95) aldıkları hizmetten memnun olduğu ve ihtiyaçlarının karşılandığı tespit edilmiştir. Bu yaklaşıma getirilen eleştiriler ise ruh sağlığı sorunlarının yaygınlığı ve yüklerinin tespitinin kısıtlı veriden gelmesi, batı kültürlerinde geliştirilen tanı sınıflamalarının ve müdahalelerin uygulanması, ruh sağlığı bozukluları epidemiyolojsinin sosyal sorunların önüne geçmesi, hizmet açığını kapatmak için sadece tedavi boşluğuna odaklanıp toplum temelli hizmetleri göz ardı etmesidir.…”
Section: Mülteci Ruh Sağlığında Global Ruh Sağlığı Yaklaşımıunclassified